Transferase Activity of Lactobacillal and Bifidobacterial β-Galactosidases with Various Sugars as Galactosyl Acceptors - Sheryl Lozel Arreola (2018)
© 2016 American Chemical Society. The β-galactosidases from Lactobacillus reuteri L103 (Lreuβgal), Lactobacillus delbrueckii subsp. bulgaricus DSM 20081 (Lbulβgal), and Bifidobacterium breve DSM 20281 (Bbreβgal-I and Bbreβgal-II) were investigated in detail with respect to their propensity to transfer galactosyl moieties onto lactose, its hydrolysis products D-glucose and D-galactose, and certain sugar acceptors such as N-acetyl-D-glucosamine (GlcNAc), N-acetyl-d-galactosamine (GalNAc), and L-fucose (Fuc) under defined, initial velocity conditions. The rate constants or partitioning ratios (kNu/kwater) determined for these different acceptors (termed nucleophiles, Nu) were used as a measure for the ability of a certain substance to act as a galactosyl acceptor of these β-galactosidases. When using Lbulβgal or Bbreβgal-II, the galactosyl transfer to GlcNAc was 6 and 10 times higher than that to lactose, respectively. With lactose and GlcNAc used in equimolar substrate concentrations, Lbulβgal and Bbreβgal-II catalyzed the formation of N-acetyl-allolactosamine with the highest yields of 41 and 24%, respectively, as calculated from the initial GlcNAc concentration.